Implementation of community based tourism principle in Pringgondani Tourism Village, Balikpapan - Nawang Retno Dwiningrum; Ranti Rustika; Febby Rio Pratama; Basri Basri (Journal of Rural Tourism, 2027)
Purpose - This study aims to analyze the implementation of Community-Based Tourism (CBT) principles in Pringgondani Tourism Village, Teritip, Balikpapan.Design/methodology/approach - This study employed a qualitative descriptive method using interviews, observations, and documentation techniques for data collection.Findings - The findings reveal that the implementation of Community-Based Tourism in Pringgondani Tourism Village has been evident since its establishment through collaboration among the landowner, PT GSA as the tourism village manager, and local MSMEs. The involvement of MSMEs has strongly supported the CBT concept. Economically, the tourism village has generated new employment opportunities, including MSME operators, parking attendants, and other supporting roles, while also increasing local community income. Socially, the increased income has contributed to improved quality of life, with no indication of gender discrimination between male and female participants. Culturally, the tourism village promotes traditional Indonesian cuisine and diverse cultural attire. Environmentally, the area has maintained its natural greenery and implemented effective waste management practices. Politically, no resistance or conflict has emerged because local communities have been actively involved since the initial planning and management stages of the tourism village.Research limitations/implications - This study is limited to a single tourism village context; therefore, the findings may not be generalizable to other tourism destinations with different socio-cultural and economic characteristics. Future studies are encouraged to conduct comparative analyses across multiple tourism villages. Practical implications - The study provides insights for tourism managers, policymakers, and local stakeholders regarding the importance of community participation and collaboration in achieving sustainable tourism development through the CBT approach. Originality/value - This study contributes to the growing literature on Community-Based Tourism by highlighting the integrated economic, social, cultural, environmental, and political dimensions of CBT implementation in a tourism village context in Indonesia.